Psychometric properties and validation of the Portuguese version of the Anxiety Control Questionnaire Revised (ACQ-R) - Suso-Ribera, Carlos (2021)
Early experiences appear to influence the sense of unpredictability and uncontrollability of both life events and emotions in vulnerable individuals. The perception of low control has been considered a general psychological vulnerability factor in emotional disorders. One of the most commonly used measures of perceived control is the Anxiety Control Questionnaire-Revised (ACQ-R). However, its internal structure has shown structural inconsistencies among several studies finding two or three factors. Our aim is to analyze the internal structure of the Portuguese adaptation of the ACQ-R in a general population sample of 267 individuals, in a confirmatory way, as well as to explore sources of validity evidence (i.e., correlations with the Depression Anxiety Stress Scales and the Positive and Negative Affect Schedule). A three-factor solution showed the best data fit(chi(2) = 150.12, degrees of freedom = 87, p < .0001, Root Mean Square Error Approximation = 0.052, 90% Confidence Interval = 0.038-0.066, Confirmatory Fit Index = 0.935, Tucker Lewis Index = 0.921). We found moderate positive correlations between the ACQ-R dimensions and anxiety, depression, stress, and negative affect, as well as between small and moderate negative associations with positive affect. All measures presented satisfactory Cronbach alphas (from .77 to .92). The Portuguese version of the ACQ-R showed good psychometric properties and the same internal structure of its original version.